1998
DOI: 10.1111/j.1445-2197.1998.tb04811.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Diagnostic Challenge of Acute Appendicitis: Evaluation Through Modified Alvarado Score

Abstract: Background: Acute appendicitis with protean manifestations may simulate almost any other acute abdominal illness and in turn may be mimicked by a variety of conditions. Progression of symptoms and signs is usual in contrast to the fluctuating course of some other diseases that lead to heavy morbidity and mortality. Methods: A practical score for the early diagnosis of acute appendicitis was established by Alvarado in 1986 and was assessed in this study for its accuracy in pre-operative diagnosis. The usefulnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
0
11

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 3 publications
1
40
0
11
Order By: Relevance
“…Modified Alvarado Score was neither sensitive nor specific in our study. There are studies who agree or disagree with modified Alvarado Score as its usefulness as a reliable prediction system for preoperative diagnosis of acute appendicitis 14,6,11 . In our study many of the parameters are not commonly found, thereby lower scoring of Modified Alvarado score .Lower scoring may be the result of inability of the patient to define the symptoms well for low socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Modified Alvarado Score was neither sensitive nor specific in our study. There are studies who agree or disagree with modified Alvarado Score as its usefulness as a reliable prediction system for preoperative diagnosis of acute appendicitis 14,6,11 . In our study many of the parameters are not commonly found, thereby lower scoring of Modified Alvarado score .Lower scoring may be the result of inability of the patient to define the symptoms well for low socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…En muchos hospitales, aun los exámenes más simples no se encuentran disponibles las 24 h del día 2,6,10,11,[14][15][16][17][18] , o no se relacionan con la presentación clínica y hallazgos de laboratorio 9,15 . Las puntuaciones diagnósticas de AA han demostrado su valor cuando se incorporan en la práctica clínica rutinaria [27][28][29][30][31][32][33][34][35][36] . Este estudio fue diseñado con el propósito de probar la exactitud diagnósti-ca y la real utilidad de la PDA aplicada por profesionales de la salud no-médicos.…”
Section: Discussionunclassified
“…A pesar de este abordaje tecnológico todavía se operan apéndices normales y perforados 3,15 . Estas consideraciones han llevado al desarrollo de puntuaciones diagnósticas de AA, diseñadas para mejorar el diagnóstico y tratamiento precoz de AA y reducir las tasas de apendicectomías en blanco y perforadas 6,[27][28][29][30][31][32][33][34][35][36] , ambas circunstancias tienen consecuencias en términos de complicaciones, costos e implicaciones legales 3,37 . La más conocida de estas puntuaciones es el Score de Alvarado (SA) 32 .…”
unclassified
See 1 more Smart Citation
“…reported negative appendectomy rates to be 32.5%, it has been determined that for cases with Alvarado score equal to and above 7 this rate decreases to 18.8%. Since Alvarado score is 6 or lower for 80% of the negative appendectomies, it is thought that the use of the scoring system especially for children and the elder would decrease negative appendectomy and perforations (24). In a study carried out by Zielke et.…”
Section: Discussionmentioning
confidence: 99%